2017
DOI: 10.1016/j.jpeds.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Blood Level of Inter-Alpha Inhibitor Proteins Distinguishes Necrotizing Enterocolitis From Spontaneous Intestinal Perforation

Abstract: Objective To examine circulating levels of inter-alpha inhibitor protein (IaIp) in infants with necrotizing enterocolitis (NEC), spontaneous intestinal perforation (SIP) and matched controls in order to assess the diagnostic accuracy of IaIp to differentiate NEC from SIP; and to compare receiver operating characteristics (ROC) of IaIp for NEC with C-reactive protein (CRP). Study design A p rospective, nested case control study of infants with feeding intolerance was carried out. Blood and clinical data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Ng, et al, used genomics to differentiate the two entities, reporting both differentially expressed mRNA as well as micro-RNAs in the small bowel tissue of NEC and SIP compared with surgical control tissue (79, 80). Shah et al used a more clinically applicable serum biomarker to distinguish NEC from SIP, called inter-alpha inhibitor proteins (IaIps) (81). IaIps are serine protease inhibitors that act as negative acute phase reactants, consumed as they protect from damaging proteases that are released into circulation during acute inflammation (81).…”
Section: Biomarkers: Disease Discriminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ng, et al, used genomics to differentiate the two entities, reporting both differentially expressed mRNA as well as micro-RNAs in the small bowel tissue of NEC and SIP compared with surgical control tissue (79, 80). Shah et al used a more clinically applicable serum biomarker to distinguish NEC from SIP, called inter-alpha inhibitor proteins (IaIps) (81). IaIps are serine protease inhibitors that act as negative acute phase reactants, consumed as they protect from damaging proteases that are released into circulation during acute inflammation (81).…”
Section: Biomarkers: Disease Discriminationmentioning
confidence: 99%
“…Shah et al used a more clinically applicable serum biomarker to distinguish NEC from SIP, called inter-alpha inhibitor proteins (IaIps) (81). IaIps are serine protease inhibitors that act as negative acute phase reactants, consumed as they protect from damaging proteases that are released into circulation during acute inflammation (81). An earlier study reported that IaIp concentrations were significantly decreased in infants with NEC compared with controls at the time of disease diagnosis (82).…”
Section: Biomarkers: Disease Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also reported changes in the level of IAIPs after stroke (Kashyap et al, 2009) and Alzheimer's disease (Shi et al, 2019), suggesting that endogenous IAIPs may be integrally related to the pathogenesis of inflammatory-related brain disorders. In addition, systemic levels of IAIPs have been reported to be decreased in sepsis in neonates and adults (Chaaban et al, 2009;Degraeuwe & Nieman, 2010;Opal et al, 2007) and in necrotizing enterocolitis in neonates (Chaaban et al, 2010;Shah et al, 2017). Sepsis and necrotizing enterocolitis are both associated with impaired neurodevelopmental outcomes in premature infants (O'Shea, 2002;Stoll et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various specific proteins, including cytokines, measured in blood, urine, and stool, have been evaluated, but most have poor specificity for making an accurate diagnosis . However, blood inter‐alpha inhibitor proteins are able to distinguish NEC from SIP and NEC from matched controls with feeding intolerance . Another potentially useful biomarker may be intestinal fatty acid‐binding protein (I‐FABP) which displays high specificity, albeit moderate sensitivity .…”
Section: Defining Nec and Utility Of Biomarkersmentioning
confidence: 99%